2012
DOI: 10.1007/s00214-012-1188-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DFT functionals on the predicted magnesium–DNA interaction: an ONIOM study

Abstract: We investigate the descriptions of several density functional theory functionals in modeling the interactions between DNA and magnesium, the divalent cation with the largest intracellular concentration. Precisely, the metal-induced proton transfer (PT) in the guanine-cytosine base pairs is analyzed within an hybrid two-layers QM/QM approach (ONIOM) by combining several functionals: BP86, B3LYP, B97-D, xB97x-D and M06-2X, as well as the MP2 approach. The aqueous environment is simulated through, on the one hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 125 publications
(124 reference statements)
0
17
0
1
Order By: Relevance
“…In the literature there is discussion about the functional that must be used in these types of systems 16. 4952 The authors of refs. 50, 51 have shown that the H‐bond lengths are overestimated from the B3LYP functional, but those of ref.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature there is discussion about the functional that must be used in these types of systems 16. 4952 The authors of refs. 50, 51 have shown that the H‐bond lengths are overestimated from the B3LYP functional, but those of ref.…”
Section: Methodsmentioning
confidence: 99%
“…The subtractive nature of the ONIOM method means that undefined terms in the MM expression do not contribute to the overall energy if the relevant atoms are entirely within the QM region, making it ideally suited for the purposes of the current study. We note that this approach has been widely adopted for QM/MM studies of DNA and related structures 3032 . Pure molecular mechanics (MM) geometry optimisation was also performed using the GROMACS simulation package 33 and the AMBERParmbsc0 force field 34 , including RESP charges derived for modified bases in our previous work 19 , in explicit aqueous phase, specifically TIP3P water 35 with Na + and Cl - counter ions to create a neutral system.…”
Section: Computational Methodologymentioning
confidence: 99%
“…[12][13][14][15][16] 碱基对内 质子转移反应受到多种环境因素的影响, 水溶剂、 碱基序列、 堆积效应和各种离子等都会影响碱基对 内质子转移. 因此科学家开始关注这些环境因素的 作用, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] 目前的研究结果表明, 水分子有助于碱基 对阴离子发生单质子转移反应, 17,18 不同碱基排序对 碱基对阴离子的单质子转移分别起到促进和阻碍 作用, 19 堆积效应在质子转移过程中改变氢键键长 并保持碱基对的平面性, 20 一些金属离子也有助于 单质子转移反应的发生. 32 Table 2 Charge…”
Section: 引 言unclassified